Difficult Central Venous Cannulation under Laryngeal Mask Airway Anesthesia in Adolescent - Kumar, D.; Suleman, M.; Shaikh, F.; Ebrahim, S. (Kathmandu University Medical Journal, 2020)
We report a case of difficult central venous cannulation under general anesthesia with laryngeal mask airway in a young female child. Our case demonstrated a difficulty in surgically finding the right internal jugular vein due to neck veins displacements by laryngeal mask airway, which caused morbidity such as prolonged surgical duration and excessive blood loss. Once the laryngeal mask airway was replaced with endotracheal tube, the internal jugular vein appeared on surface and procedure was successfully completed in a few minutes. Such difficulties warrant an alternate approach in airway management in order to prevent major adverse effects.